Juvenile courts: creating (an atmosphere of) understanding - Van der Houwen, Fleur; Jol, Guusje (Language and Law / Linguagem e Direito, 2017)
In this paper we examine Dutch court proceedings according to juvenile criminal law. Several international treaties and agreements such as the ‘Beijing Rules’ (1989) acknowledge the dierent status of juveniles and emphasize that legal professionals have special obligations in case adolescents become a suspect. An important task for the legal system is to create an atmosphere of understanding and facilitate adolescents understanding the proceedings. This seems clear, but how do legal professionals orient to the task in real interaction and how is this interactionally constructed? In order to answer these questions, we take a qualitative approach and analyze videotapes of Dutch criminal trials in which the suspects are adolescents. Based on extracts from these court proceedings, we show how judges can orient to the special status of juveniles while interacting with them and specically how they create (an atmosphere of) understanding.